2021
DOI: 10.1186/s12912-021-00575-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three interactive examination designs in active learning classrooms for nursing students

Abstract: Background Despite the advantages of using active learning strategies in nursing education, researchers have rarely investigated how such pedagogic approaches can be used to assess students or how interactive examinations can be modified depending on circumstances of practice (e.g., in online education). Aims The aim was to compare three interactive examination designs, all based on active learning pedagogy, in terms of nursing students’ engagement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…These results were in line with the results of other studies that reported that written exams, oral exams, and presentations of assignments were the most popular elections for students' evaluation purposes. (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with the results of other studies that reported that written exams, oral exams, and presentations of assignments were the most popular elections for students' evaluation purposes. (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…To that end, the EBTPs explored in this review created positive environments that were conducive to student learning. Students' perceptions gathered through survey responses revealed positive attitudes towards various aspects of learning components: teamwork (Brown, 2016;Huitt et al, 2015;Tarhan & Ayyildiz, 2015); usefulness of resources in learning (Fyfe, Fyfe, Dye, & Radley-Crabb, 2018); learning experiences (Abraham, Vashe, & Torke, 2015;Chen, Kelly, Hayes, Van Reyk, & Herok, 2016;Derfoufi et al, 2015;Gorres-Martens et al, 2016;Kulak & Newton, 2015;Matsuda, Azaiza, & Salani, 2017;Muthukrishnan et al, 2019;Youngwanichsetha, Kritcharoen, Chunuan, Kala, & Phumdoung, 2020); interest in biochemistry (Tarhan & Ayyildiz, 2015); accessibility to the instructor (Gonzalez & Gadbury-Amyot, 2016), cognitive load (Gross, Wright, & Anderson, 2017); engagement in scientific inquiry (Brown, 2016); experiment instructions (King et al, 2016); relevance of the teaching practices (King et al, 2016); exam experience (Ahlstrom & Holmberg, 2021); empathy towards older persons (Lucchetti, Duarte, Assis, Laurindo, Lucchetti, 2019); enjoyment (Kukolja Taradi & Taradi, 2016), and use of technology (Hardie et al, 2020).…”
Section: Positive Attitudesmentioning
confidence: 99%
“…Through user-friendly interfaces, interactive quizzes, videos, and gamified elements, patients can learn and practice essential self-care behaviors in an enjoyable and stimulating manner [ 11 ]. The incorporation of interactive features fosters greater knowledge retention and application, encouraging patients to apply what they have learned in real-life situations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%